Does the Epstein–Barr Virus Play a Role in the Pathogenesis of Graves’ Disease? - Pyzik, Aleksandra (Int J Mol Sci, 2019)
Graves’ disease (GD) it the most common chronic organ-specific thyroid disorder without a fully recognized etiology. The pathogenesis of the disease accounts for an interaction between genetic, environmental, and immunological factors. The most important environmental factors include viral and bacterial infections. The Epstein-Barr virus (EBV) is one of the most common latent human viruses. Literature has suggested its role in the development of certain allergic and autoimmune diseases. EBV also exhibits oncogenic properties. The aim of the study was to analyze and compare the presence of EBV DNA in peripheral blood mononuclear cells (PBMCs) in patients with newly recognized GD and to find a correlation between EBV infection and the clinical picture of GD. The study included 39 untreated patients with newly diagnosed GD and a control group of 20 healthy volunteers who were gender and age matched. EBV DNA was detected with reverse transcription polymerase chain reaction (RT PCR) assay. The studies showed a significantly higher incidence of EBV copies in PBMCs among GD patients compared to the control group. Whereas, no significant correlations were found between the incidence of EBV copies and the evaluated clinical parameters. Our results suggest a probable role of EBV in GD development. EBV infection does not affect the clinical picture of Graves’ disease.